2020
DOI: 10.1177/1120700020938029
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis after hip fracture: higher mortality than the general population and delayed surgery increases the risk at any time

Abstract: Purpose: To estimate survival curves in patients with hip fracture according to gender, age, type of fracture, and waiting time for surgery and to compare them with the life expectancy of the general population. The study hypothesis is that survival after hip fractures is significantly lower than in the general population, especially in cases that underwent delayed surgery, regardless of age and gender. Methods: A survival analysis study was designed and approved by our institutional ethics review board. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Moreover, patients included in the FLS protocol in our department had an adjusted 1-year mortality hazard ratio lower than those individuals treated before its implementation. A recent survival analysis showed that hip fracture patients had a lower life expectancy compared to the general population and their high risk of dying remained constant [ 10 ]. A larger study also showed that hip fracture is associated with excess short- and long-term all-cause mortality in both sexes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients included in the FLS protocol in our department had an adjusted 1-year mortality hazard ratio lower than those individuals treated before its implementation. A recent survival analysis showed that hip fracture patients had a lower life expectancy compared to the general population and their high risk of dying remained constant [ 10 ]. A larger study also showed that hip fracture is associated with excess short- and long-term all-cause mortality in both sexes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…While surgical treatment was performed in approximately 80% of patients with osteoporotic hip fractures within the first 24 h, this was the case in only approximately 65% of patients with a pathologic fracture. While delay in time to surgery is known to be directly correlated with mortality in patients with osteoporotic hip fractures, the delay in patients suffering from pathologic femoral fractures was not associated with an increased mortality rate during the acute hospital stay in the present analysis [ 25 ]. Therefore, it must be presumed that pathologic hip fractures in geriatric patients are—other than fractures in osteoporosis-related hips—not a typical frailty marker, as is already known from other hip fracture types, e.g., periprosthetic femoral fractures [ 26 ].…”
Section: Discussionmentioning
confidence: 85%
“… 14 Delayed diagnosis of hip fractures and resultant prolonged time to hospital admission and corrective surgery have been demonstrated to increase patient mortality and morbidity. 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%